2017
DOI: 10.4062/biomolther.2016.219
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Urotensin II Receptor Antagonist, KR-36996 Inhibits Smooth Muscle Proliferation through ERK/ROS Pathway

Abstract: Urotensin II (UII) is a mitogenic and hypertrophic agent that can induce the proliferation of vascular cells. UII inhibition has been considered as beneficial strategy for atherosclerosis and restenosis. However, currently there is no therapeutics clinically available for atherosclerosis or restenosis. In this study, we evaluated the effects of a newly synthesized UII receptor (UT) antagonist, KR-36996, on the proliferation of SMCs in vitro and neointima formation in vivo in comparison with GSK-1440115, a know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Cells were seeded in a 96-well plate at a density of 0.5 × 10 5 cells/well. Sixteen hours after plating, cells were treated with BDB at various concentrations and after 1 h, cells were exposed to UVB light and incubated for 24 h. After the addition of DCF-DA (25 μM) (Sigma-Aldrich Co., St. Louis, MO, USA), the fluorescence of 2′,7′-dichlorofluorescein was detected using a spectrofluorometer [ 34 ]. The ROS detection was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded in a 96-well plate at a density of 0.5 × 10 5 cells/well. Sixteen hours after plating, cells were treated with BDB at various concentrations and after 1 h, cells were exposed to UVB light and incubated for 24 h. After the addition of DCF-DA (25 μM) (Sigma-Aldrich Co., St. Louis, MO, USA), the fluorescence of 2′,7′-dichlorofluorescein was detected using a spectrofluorometer [ 34 ]. The ROS detection was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…As is well known, the MAPK family is composed of ERK1/2, JNK, and p38. A growing body of evidence has demonstrated that ROS-ERK1/2 cascades participate in the regulation of VSMC proliferation in vitro and neointima formation in vivo [35][36][37]. Previous studies also showed that JNK, p38, and ERK1/2 phosphorylation acted a critical role in high-glucose-induced oxidative injury and VSMC proliferation [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In THP‐1 monocytes, MAPK1/3 induces activation of the IL‐1ß pathway, which in turn downregulates expression of ABCA1, which speeds up foam cell formation leads to atherosclerotic lesions (Kim et al 2017a). Kim et al (2017a, b) reported that UTR activation by urotensin‐II induces ROS generation and MAPK1/3 activation in vascular smooth muscle cells, which are associated with atherosclerosis and restenosis (Kim et al 2017b). urotensin‐II stimulates UTR and induces the overexpression of 5‐lipoxygenase (ALOX5) protein and release of leukotriene B4 (LTB4) via ROS/AKT pathways, which initiates macrophage activation and promotes atherosclerosis in mouse RAW264.7 macrophages (Lu et al 2019).…”
Section: Summary Of the Urotensin Pathway Mapmentioning
confidence: 99%